2003
DOI: 10.1046/j.1360-0443.2003.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of federal ephedrine and pseudoephedrine regulations on methamphetamine‐related hospital admissions

Abstract: Regulations targeting precursors used by large-scale producers reduced admissions substantially during the study period. However, the regulation of precursors used primarily by small-scale producers had little, if any, effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 18 publications
7
116
0
1
Order By: Relevance
“…Indeed, enforcement activities have had a limited impact on the supply of illegal substances imported from South East Asia and Central America . With respect to the banning of precursor chemicals, similar bans have been in place in the U.S. since 1996 and, though temporary disruptions to methamphetamine drug markets have been observed, use of methamphetamine has nevertheless grown unabated Cunningham & Liu, 2003;Reuter, 2003). Therefore, there is an urgent need for evidence-based HIV prevention and drug treatment programs for crystal methamphetamine injectors in order to minimize the harms associated with use of this drug (Reuter, 2003;Kerr et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, enforcement activities have had a limited impact on the supply of illegal substances imported from South East Asia and Central America . With respect to the banning of precursor chemicals, similar bans have been in place in the U.S. since 1996 and, though temporary disruptions to methamphetamine drug markets have been observed, use of methamphetamine has nevertheless grown unabated Cunningham & Liu, 2003;Reuter, 2003). Therefore, there is an urgent need for evidence-based HIV prevention and drug treatment programs for crystal methamphetamine injectors in order to minimize the harms associated with use of this drug (Reuter, 2003;Kerr et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal methamphetamine injection was independently associated with syringe sharing, indicating the potential for increased HIV transmission as popularity of this drug increases. Since changing the penalties for methamphetamine production and the banning of precursor chemicals are likely to have a negligible impact on the use of this drug Cunningham & Liu, 2003;Reuter, 2003), evidence-based interventions are urgently needed to address the severe potential harms for individuals who inject crystal methamphetamine. The crude proportion of individuals reporting crystal methamphetamine injection during the six months prior to the interview for each year between 1997 and 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine purity in the US has varied dramatically over the last 15 years with multiple peaks and valleys (Caulkins et al, 2004), very possibly driven at least in part by successive waves of precursor regulations (Cunningham and Liu, 2003).…”
Section: Illicit Drugs Are Of Varying Qualitymentioning
confidence: 99%
“…In addition, a few empirical studies have examined the impact of precursor regulation at the federal level on methamphetamine arrests (Cunningham & Liu, 2005) and methamphetamine-related hospital admissions (Cunningham & Liu, 2003a). Both studies found positive associations between precursor restriction laws and reductions in methamphetamine-related legal and medical incidents.…”
Section: Methamphetamine Use Manufacture and Associated Dangersmentioning
confidence: 99%